2001
DOI: 10.1038/labinvest.3780302
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Germ Cell Maturation Stage-Specific Markers in Spermatocytic Seminoma: Diagnostic and Etiological Implications

Abstract: SUMMARY:It is generally accepted that testicular seminomas and spermatocytic seminomas have separate pathogeneses, although the origin of these two types of germ cell tumors of the adult testis remains a matter of debate. Although an embryonic germ cell origin seems to be most likely for seminomas, a spermatogonia-spermatocyte origin has been suggested for spermatocytic seminoma. To shed more light on the etiology of spermatocytic seminomas, we undertook an immunohistochemical and molecular approach using SCP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 36 publications
7
70
0
Order By: Relevance
“…Furthermore, it has been demonstrated that certain histologic types express markers associated with distinct maturational stages of germ cell development, which presumably are dependent on a specific gonadal environment. 7,[43][44][45] Lastly, there are some data suggesting that the chromosomal marker characteristic of testicular germ cell tumors, the isochromosome 12p, plays only a minor role in CNS-GCTs. 18,22 As a consequence, it must be debated whether the information generated in the more frequent (and more easily assessable) testicular germ cell tumors can indeed be transferred to CNS-GCTs without scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that certain histologic types express markers associated with distinct maturational stages of germ cell development, which presumably are dependent on a specific gonadal environment. 7,[43][44][45] Lastly, there are some data suggesting that the chromosomal marker characteristic of testicular germ cell tumors, the isochromosome 12p, plays only a minor role in CNS-GCTs. 18,22 As a consequence, it must be debated whether the information generated in the more frequent (and more easily assessable) testicular germ cell tumors can indeed be transferred to CNS-GCTs without scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, spermatocytic seminomas still exhibit similarities to cells belonging to the germ cell lineage (Burke and Mostofi, 1993;Cummings et al, 1994;Eble, 1994). They have a different etiology and clinical behavior from TGCT (Burke and Mostofi, 1993;Dekker et al, 1992;Looijenga et al, 1994;Rosenberg et al, 1998;Stoop et al, 2001). Available data suggest that spermatocytic seminomas originate from a later developmental stage of the germ cell than TGCT, most likely spermatocytes (Burke and Mostofi, 1993;Dekker et al, 1992;Eble, 1994;Muller et al, 1987;Romanenko and Persidskii, 1983;Rosai et al, 1969;Talerman, 1974Talerman, , 1980Talerman et al, 1984;).…”
Section: Discussionmentioning
confidence: 99%
“…However, we recently found indications that the cell of origin of spermatocytic seminoma might be at an earlier stage of development than spermatocytes. This cell is capable of further maturation and partial meiosis (Looijenga et al, 1994;Rosenberg et al, 1998;Stoop et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic studies on spermatocytic seminoma are few; it appears that the most common chromosomal abnormality is gains in chromosome 9. 2 A combined immunohistochemical and molecular study by Stoop et al 81 supports that these tumors are likely to originate in a cell farther along the developmental pathway than those that give rise to other germ cell tumors.…”
Section: Molecular Biology Of Germ Cell Tumorsmentioning
confidence: 99%